Membrane hyperpolarization drives cation influx and fungicidal activity of amiodarone - Maresova, Lydie; Muend, Sabina; Zhang, Yong-Qiang; Sychrova, Hana; Rao, Rajini (The Journal of biological chemistry, 2009)
Cationic amphipathic drugs, such as amiodarone, interact preferentially with lipid membranes to exert their biological effect. In the yeast Saccharomyces cerevisiae, toxic levels of amiodarone trigger a rapid influx of Ca(2+) that can overwhelm cellular homeostasis and lead to cell death. To better understand the mechanistic basis of antifungal activity, we assessed the effect of the drug on membrane potential. We show that low concentrations of amiodarone (0.1-2 microm) elicit an immediate, dose-dependent hyperpolarization of the membrane. At higher doses (>3 microm), hyperpolarization is transient and is followed by depolarization, coincident with influx of Ca(2+) and H(+) and loss in cell viability. Proton and alkali metal cation transporters play reciprocal roles in membrane polarization, depending on the availability of glucose. Diminishment of membrane potential by glucose removal or addition of salts or in pma1, tok1Delta, ena1-4Delta, or nha1Delta mutants protected against drug toxicity, suggesting that initial hyperpolarization was important in the mechanism of antifungal activity. Furthermore, we show that the link between membrane hyperpolarization and drug toxicity is pH-dependent. We propose the existence of pH- and hyperpolarization-activated Ca(2+) channels in yeast, similar to those described in plant root hair and pollen tubes that are critical for cell elongation and growth. Our findings illustrate how membrane-active compounds can be effective microbicidals and may pave the way to developing membrane-selective agents.
Keywords: Ion Transport; Saccharomyces cerevisiae; membránové proteiny; Amiodarone; iontový transport; Humans; Membrane Proteins; fluorescence; Fluorescence; imunoprecipitace; lidé; Immunoprecipitation; amiodaron